Geology, Terrain Morphometry, and Environmental Patterns of the Belezma–Batna Anticline (Northeastern Algeria): An Integrated Remote Sensing and GIS Analysis - Djeffal , Rami; Youcef Brahim, El Hadj (International Journal of Aquatic Research and Environmental Studies, 2026)
The Belezma–Batna anticline, located within the Pre-Atlasic domain of northeastern Algeria, represents a structurally controlled mountain system characterized by pronounced relief, complex drainage organization, and heterogeneous vegetation cover. This study applies an integrated geomorphometric and remote sensing approach to investigate the relationships between geological structure, terrain morphology, hydrological organization, and vegetation distribution within the massif. Digital elevation data derived from the Shuttle Radar Topography Mission (SRTM) and multispectral Sentinel-2 imagery were processed using Google Earth Engine and GIS techniques. Terrain morphometric parameters, including slope, Topographic Position Index (TPI), terrain curvature, and Relative Elevation Index (REI), were derived from the DEM, while drainage organization was evaluated using HydroSHEDS flow accumulation data and drainage density analysis. Vegetation patterns were assessed using the Normalized Difference Vegetation Index (NDVI). The results reveal a strongly structured mountainous landscape dominated by an elongated ENE–WSW ridge system corresponding to the axis of the Belezma–Batna anticline. Slope values range from 0° to 43.84° with a mean of 6.84°, highlighting pronounced topographic contrasts between the central ridge and surrounding piedmont areas. Morphometric analyses demonstrate that resistant carbonate formations form elevated ridge systems, whereas weaker marl-rich and siliciclastic units preferentially occupy valleys and structural depressions. Drainage analysis indicates a predominantly dendritic to sub-dendritic network strongly influenced by ridge–valley morphology and structural orientation. A weak negative correlation between slope and drainage density (r = −0.208) suggests that drainage development is controlled by multiple interacting factors, including lithology, structure, and hydrological conditions. NDVI values reveal clear spatial relationships between vegetation distribution, topography, and environmental gradients, with dense vegetation concentrated in mountainous sectors and lower vegetation cover characterizing peripheral plains. The integrated results demonstrate that the geomorphology of the Belezma–Batna anticline is governed by the interaction of tectonic structure, lithological resistance, fluvial erosion, and eco-hydrological processes. The study highlights the effectiveness of combining geomorphometric analysis and satellite remote sensing for investigating structurally controlled mountain environments and contributes to a better understanding of landscape organization within the Pre-Atlasic domain of northeastern Algeria.
Keywords: Belezma–Batna anticline; geomorphometry; remote sensing; SRTM; Sentinel-2; drainage density; NDVI; morphotectonics; northeastern Algeria